Analisis Prosedur Sistem Informasi Akuntansi Pembayaran Pinjaman Karyawan Pada PT. PD. Paya Pinang - Nirwana Putri; Aqwa Naser Daulay (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this research is to determine and analyze the application of accounting information systems in supporting employee loan payment procedures at PT. PD. Paya Pinang and to find out whether PT employee loan payments. PD. Paya Pinang is in accordance with the accounting information system created by the company. The problem faced by the company is how to implement the accounting information system mechanism in PT loan payments. PD. Paya Pinang, whether the company's procedure book complies with events in the field. This study uses a qualitative method. This research analyzes how loan payment procedures are carried out in the accounting information system at PT.PD. Paya Pinang with stages in the form of problem identification, data collection and data analysis. This research was carried out at PT. PD. Paya Pinang on Jl. Samanhudi No.15 from January to February 2023. Data collection used interview and documentation methods. The results of the discussion obtained are that every loan given to each employee will go through procedures that have been determined by the company concerned, this is what the company PT. PD. Paya Pinang.